Behaviour Of Coking Process In Catalytic Combustion Of Ethylacetate nd Benzene In Air Over Cr-ZSM-5 Catalyst. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (Institut Piawaian dan Penyelidikan Perindustrian Malaysia, 2004)
The coking behaviour and kinetic study of Cr-ZSM-5 (Si/Al=240) catalyst during ethyl acetate (EAc) and benzene (Bz) combustion are reported.